Experimental investigations on the vertical distribution and properties of oil-mineral aggregates (OMAs) formed by different clay minerals. (1st June 2022) - Yu, Yue; Qi, Zhixin; Xiong, Deqi; Li, Wenxin; Yu, Xinping; Sun, Ruiyang
Abstract: After oil spills, the floating oil may interact with suspended minerals to form the oil-mineral aggregates (OMAs) in turbulent environments. In this work, a flume was used in conjunction with a settling device to investigate the vertical distribution and properties of OMAs formed by different clay minerals. The density and size of OMAs depend on the density and surface properties of the constituent particles, which also affect the vertical distribution of dispersed oil. Density of oil-montmorillonite aggregates increased from 1165 to 1897 kg/m 3 within 6 h test. Among the four minerals, montmorillonite displayed the highest affinity with dispersed oil and the most significant modification of oil-water interfacial tension. Oil dispersion efficiency was significantly greater and reached 39.3% in the presence of montmorillonite at 300 mg/L compared with the control group (17.6%). Particle concentration is the most important factor for the capture of oil and participation of particles during the OMA formation, while the zeta potential and hydrophobicity have nonsignificant effect on the two processes. Cation exchange capacity has a moderate effect on the sunken oil formation, which is also the second main factor governing the particle participation. Particle size plays a second leading role in governing the sunken oil formation but with a minor contribution of the particle participation. Highlights: Montmorillonite is the most effective granular material to promote the dispersion and sinking process of spilled oil. The density and swelling behavior of particle govern the OMA density and the distribution of dispersed oil. The hydrophobicity and size of particle work in concert to influence the size of trapped oil and OMAs. Particle concentration is the most important factor for the sunken oil formation.